Comparison of Signal Strengths of 2G/3G/4G Services on a University Campus - Begüm KORUNUR ENGIZ; Çetin KURNAZ (International Journal of Applied Methods in Electronics and Computers, 2016)
This study aims to determine the signal strengths of three cellular system operators for 2G, 3G and 4G services on the basis of drive test measurements that were conducted twice on a specific route on Ondokuz Mayis University (OMU) Kurupelit Campus. Nine same brand and model smartphones with “Android” operating system and “Netmonitor” application were used during the synchronized measurements. Measurement results demonstrate that 2G signal strengths are significantly higher than 3G/4G, and the received signal strength can change depending on the location, frequency, line of sight, and base stations’ output power. Considering all operators and both of the measurement results; the signal strengths vary from -50dBm to -103dBm for 2G, while from -51dBm to -113dBm, and from -62dBm to -130dBm for 3G and 4G respectively. The average signal strengths of both measurements for 2G, 3G and 4G vary between -79.25dBm and -63.36, -87.22dBm and -74.51dBm, -105.88dBm and -88.36dBm. The second measurement results show that the quality of signal is lower than the minimum limit (<-100dBm) determined by Information and Communication Technologies Authority (ICTA) of Turkey for 2G at some measurement locations. Furthermore, for 3G lower than the limit at 4.2% of all measurement locations for Operator C while for 4G 70.9% for Operator A. The use and comparison of these measurement results help operators to determine the parts that need enhancement, and take further actions.